Changes in alcohol use and heavy episodic drinking in U.S. Women of childbearing-age and peripartum between 2001–2002 and 2012–2013. (August 2020) - Tebeka, Sarah; De Premorel Higgons, Alix; Dubertret, Caroline; Le Strat, Yann
Highlights: Prevalence of at least one alcohol drink increased in childbearing-aged women. Prevalence of heavy episodic drinking increased in childbearing-aged women. Alcohol use have even dramatically increased in U.S. pregnant and postpartum women. Abstract: Background: Heavy episodic drinking (HED) is a frequent pattern of alcohol use in women of childbearing age with severe consequences for both women and child, making it a major public health issue. Some states in the US have reported laws that target the use of alcohol during pregnancy. Our aim was to examine the evolution of 12-month alcohol use and 12-month HED prevalence in childbearing age, pregnant and postpartum women between 2001 and 2002 and 2012–2013. Methods: Our data were drawn from the National Epidemiologic Study of Alcohol and Related Conditions (NESARC) conducted in 2001–2002 and NESARC-III conducted in 2012–2013, two independent, representative samples of U.S. population. Past-year alcohol use and HED was evaluated according face-to-face interview for all participants. Results: Our sample consisted of 24, 536 women of childbearing age, including 2846 pregnant and postpartum women. Prevalence of 12-month alcohol use increased from 2001 to 2002 to 2012–2013, in both childbearing-aged women (66.14% to 75.48%; aOR = 1.62, 95%CI = 1.46–1.80) and pregnant and postpartum women (57.81% to 66.19%; aOR = 1.56, 95%CI = 1.25–1.94). Prevalence of 12-month HED increased from 2001 to 2002 to 2012–2013, in both childbearing-aged women (22.57% to 36.34%; aOR = 1.97, 95%CI = 1.79–2.16) and pregnant and postpartum women (17.85% to 28.21%; aOR = 1.84, 95%CI = 1.47–2.30). Conclusions: Alcohol use and HED increased in last 10 years in both childbearing age and pregnant and postpartum US women. That questions the impact of implemented laws, policies and alcohol guidelines in this population within the last 10 years.